WALK 2.0: Examining the effectiveness of Web 2.0 features to increase physical activity in a 'real world' setting: an ecological trial protocol. Issue 10 (10th October 2014) - Caperchione, Cristina M; Kolt, Gregory S; Savage, Trevor N; Rosenkranz, Richard R; Maeder, Anthony J; Vandelanotte, Corneel; Duncan, Mitch J; Van Itallie, Anetta; Tague, Rhys; Mummery, W Kerry
Abstract : Introduction: Low levels of health-enhancing physical activity require novel approaches that have the potential to reach broad populations. Web-based interventions are a popular approach for behaviour change given their wide reach and accessibility. However, challenges with participant engagement and retention reduce the long-term maintenance of behaviour change. Web 2.0 features present a new and innovative online environment supporting greater interactivity, with the potential to increase engagement and retention. In order to understand the applicability of these innovative interventions for the broader population, 'real-world' interventions implemented under 'everyday conditions' are required. The aim of this study is to investigate the difference in physical activity behaviour between individuals using a traditional Web 1.0 website with those using a novel Web 2.0 website. Methods and analysis: In this study we will aim to recruit 2894 participants. Participants will be recruited from individuals who register with a pre-existing health promotion website that currently provides Web 1.0 features (http://www.10000steps.org.au ). Eligible participants who provide informed consent will be randomly assigned to one of the two trial conditions: the pre-existing 10 000 Steps website (with Web 1.0 features) or the newly developed WALK 2.0 website (with Web 2.0 features). Primary and secondary outcome measures will be assessed by self-report at baseline, 3 months and 12 months, and include: physical activity behaviour, height and weight, Internet self-efficacy, website usability, website usage and quality of life. Ethics and dissemination: This study has received ethics approval from the University of Western Sydney Human Research Ethics Committee (Reference Number H8767) and has been funded by the National Health and Medical Research Council (Reference Number 589903). Study findings will be disseminated widely through peer-reviewed publications, academic conferences and local community-based presentations. Trial registration number: Australian New Zealand Clinical Trials Registry Number: ACTRN12611000253909, WHO Universal Trial Number: U111-1119-1755